Physicians' perspectives on massage therapy. - Verhoef, M. J. (College of Family Physicians of Canada, 1998)
OBJECTIVE: To examine the knowledge, opinions, and referral behaviour of family physicians with respect to massage therapy and to explore factors associated with referral. DESIGN: A random, cross-sectional mailed survey. SETTING: Alberta family practices. PARTICIPANTS: Family physicians (n = 300). MAIN OUTCOME MEASURES: A self-report survey was developed for the study. This survey contained questions about sociodemographic and practice characteristics, perceived knowledge of massage therapy, opinions about the usefulness and legislation (government regulations) of massage therapy, and referral behaviour. RESULTS: Fifty-four percent of physicians (n = 161) completed the questionnaire. Sixty-eight percent of respondents indicated they had minimal or no knowledge of massage therapy. Despite this low level of knowledge, most (83%) believed massage therapy was a useful adjunct to their own practice. Moreover, 71% had referred patients to massage therapists and most (72%) perceived increasing demand from their patients for massage therapy. Approximately half of physicians surveyed supported government regulation of massage therapy. CONCLUSIONS: Physicians demonstrated a discrepancy between their knowledge of massage therapy and their opinions of, and referrals to, the profession. Physicians who referred patients to massage therapists generally held more positive opinions and had more knowledge of the discipline.